Razširjenost in status vrst rodu gladkih plavačev, Graphoderus (Coleoptera: Dytiscidae), v Sloveniji - Ambrožič, Špela (Acta entomologica slovenica (Ljubljana), 2015)
We summarize knowledge over species status and distribution in the genus Graphoderus in Slovenia regarding historical and recent data. Systematic surveys with new sampling approaches were conducted to evaluate the current distribution of these species. There are four species of the genus Graphoderus recorded so far in Slovenia and all are relatively rare, but most frequent species being Graphoderus cinereus and G. austriacus. Other two species G. bilineatus and G. zonatus had been found in Slovenia only on few locations, the latter with no recent records. According to EU Habitat Directive two Natura 2000 sites have been designated for conservation of G. bilineatus in Slovenia. A revision of threat status on the national Red List in Slovenia is proposed for all four species.
Keywords: Graphoderus; Graphoderus bilineatus; naravovarstveno ovrednotenje; ovratniški plavač; višinska razširjenost; zgodovinski pregled